2016
DOI: 10.1161/jaha.116.004588
|View full text |Cite
|
Sign up to set email alerts
|

Early Coronary Reperfusion Facilitates Return of Spontaneous Circulation and Improves Cardiovascular Outcomes After Ischemic Cardiac Arrest and Extracorporeal Resuscitation in Pigs

Abstract: BackgroundExtracorporeal cardiopulmonary resuscitation (ECPR) is widely proposed for the treatment of refractory cardiac arrest. It should be associated with coronary angiography if coronary artery disease is suspected. However, the prioritization of care remains unclear in this situation. Our goal was to determine whether coronary reperfusion should be instituted as soon as possible in such situations in a pig model.Methods and ResultsAnesthetized pigs were instrumented and submitted to coronary artery occlus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The animals in the intervention group showed a significantly lower mean coronary perfusion pressure than those in the control group (Figure 4B). Early and adequate coronary reperfusion is important for functional recovery and for preventing myocardial damage after cardiac arrest [41][42][43]. Accordingly, the presented study found an increase in arrhythmias in the intervention group, which, on the one hand, could be interpreted as a direct effect of the proarrhythmogenic effects of hypocalcemia, and, on the other hand, as a consequence of the lower CPP, as already assumed in preliminary studies.…”
Section: Discussionsupporting
confidence: 76%
“…The animals in the intervention group showed a significantly lower mean coronary perfusion pressure than those in the control group (Figure 4B). Early and adequate coronary reperfusion is important for functional recovery and for preventing myocardial damage after cardiac arrest [41][42][43]. Accordingly, the presented study found an increase in arrhythmias in the intervention group, which, on the one hand, could be interpreted as a direct effect of the proarrhythmogenic effects of hypocalcemia, and, on the other hand, as a consequence of the lower CPP, as already assumed in preliminary studies.…”
Section: Discussionsupporting
confidence: 76%
“…This etiologic research strategy allows identification of the cause of OHCA in 59% of cases [31]. Several registries or animal studies have shown that immediate or emergent coronary angiography may improve survival of OHCA [32,33]. The overall invasive strategy implemented may therefore have contributed to the higher survival rate, although improved survival with Period 2 was still observed after several types of adjustments for the use of myocardial revascularization procedures were made.…”
Section: Discussionmentioning
confidence: 99%
“…In this specific group of patients, studies have demonstrated that coronary lesions are frequently multiple and proximal [ 68 , 69 ]. Moreover, it has been shown that the delay between CA and PCI is associated with survival [ 70 ]. If a pulmonary embolism is the origin of the CA, an injected pulmonary CT-scan should be considered to confirm the diagnosis [ 71 ].…”
Section: Patients Management After Ecprmentioning
confidence: 99%